2011
DOI: 10.1128/jb.05473-11
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the LIV System of Campylobacter jejuni Reveals Alternative Roles for LivJ and LivK in Commensalism beyond Branched-Chain Amino Acid Transport

Abstract: Campylobacter jejuni is a leading cause of diarrheal disease in humans and an intestinal commensal in poultry and other agriculturally important animals. These zoonotic infections result in significant amounts of C. jejuni present in the food supply to contribute to disease in humans. We previously found that a transposon insertion in Cjj81176_1038, encoding a homolog of the Escherichia coli LivJ periplasmic binding protein of the leucine, isoleucine, and valine (LIV) branched-chain amino acid transport system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…Unlike other enteropathogenic bacteria C. jejuni is unable to use glucose as growth substrate [35] and only a subset of C. jejuni isolates harbor a fucP gene cluster that facilitates the catabolism of fucose [36], [37]. Instead of carbohydrates, the glucogenic amino acids aspartate, asparagine, glutamate, glutamine, proline and serine represent important nutrients fueling the in vitro growth of C. jejun i [38][40], [42], [43], [45], [55], [68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other enteropathogenic bacteria C. jejuni is unable to use glucose as growth substrate [35] and only a subset of C. jejuni isolates harbor a fucP gene cluster that facilitates the catabolism of fucose [36], [37]. Instead of carbohydrates, the glucogenic amino acids aspartate, asparagine, glutamate, glutamine, proline and serine represent important nutrients fueling the in vitro growth of C. jejun i [38][40], [42], [43], [45], [55], [68].…”
Section: Discussionmentioning
confidence: 99%
“…While it is well documented that amino acids represent major energy and carbon sources for the in vitro growth of C. jejuni , only a few studies have examined the contribution of amino acid catabolism to bacterial colonization. For example, serine and aspartate catabolism were shown to be important for C. jejuni colonization of the avian gut [38], [45] and mutation of a putative branched amino acid transporter resulted in an attenuated colonization phenotype in chicken [20], [55]. The γ-glutamyltranspeptidase (GGT) dependent utilization of glutamine and glutathione by C. jejuni 81-176 supports the colonization of the murine intestine [51].…”
Section: Introductionmentioning
confidence: 99%
“…LivHMGF are membrane components that are shared between both systems (47). Previous studies have demonstrated that liv mutants in Campylobacter jejuni are unable to colonize chicks (48) and that liv mutants in Streptococcus pneumoniae are attenuated in mice (49). These studies suggest a role for leucine, isoleucine, and valine transporters in in vivo growth and pathogenesis.…”
Section: Discussionmentioning
confidence: 73%
“…Interestingly, the gene product of livK was already found upregulated in our previous proteomics study (Stahl and Ullrich, 2016). LivK is part of a branched amino acid uptake system transporting leucine, isoleucine, and valine (Adams et al, 1990;Ribardo and Hendrixson, 2011). LivK's functional involvement in branched amino acid transport in M. adhaerens HP15 is supported by the close proximity of genes encoding the inner membrane translocators LivH and LivG as well as the ATP binding components LivM and LivF (Adams et al, 1990).…”
Section: Genes Involved In Metabolic Exchange During the Interactionmentioning
confidence: 93%